EdTech-Based Educational Management Strategies in Remote Areas and Social Justice Transformation for Rural Communities - Mu’ad Amsyari; Didit Darmawan; Muhammad Yusron Maulana El-Yunusi (Metromedia, 2026)
The acceleration of educational digitalization serves as the primary pillar in overcoming learning quality disparities caused by geographical isolation in remote areas. This study aims to analyze the utilization of Educational Technology (EdTech) platforms within school operational management strategies in isolated regions while evaluating its impact on addressing educational inequality and achieving social justice. A descriptive qualitative approach using a multiple-case study design was implemented through in-depth interviews, field observations, and analysis of school operational documents. The findings indicate that successful EdTech adoption is largely determined by adaptive managerial strategies, including teacher digital literacy training, local curriculum harmonization, offline-first e-learning systems, and transparent data-analytic supervision. Integrating digital technology significantly narrows academic achievement gaps, enhances students’ digital skills, and fosters local community social commitment toward children’s educational continuity. This study concludes that combining responsive school management strategies with inclusive EdTech access represents the core foundation for realizing social justice and equitable national education quality in remote regions.